IMPLEMENTASI NILAI-NILAI PENDIDIKAN AKHLAK DALAM MENINGKATKAN KECERDASAN SPIRITUAL SANTRI DI PONDOK PESANTREN RAUDLATUL ULUM I GANJARAN GONDANGLEGI MALANG - Muhammad Izzul Latif Syam (Turatsuna : Jurnal Keislaman dan Pendidikan, 2021)
AbstractThe application of moral values in increasing spiritual intelligence in Islamic boarding schools is a priority scale. This application is carried out in a variety of activities, both formal and non-formal, considering that Islamic boarding schools now have formal education. This is done to realize religious students and morality.This is study aims to: (a) describes and analyze moral vallues in improving students 'spiritual intelligence, (b) describe and analyze the implementation of moral education values in improving students' spiritual intelligence, and (c) describe and analyze the results of the implementation of the values of the value of moral education in improving the intelligence of students.This research is a qualitative descriptive study and uses qualitative methods that prioritize phenomena experienced by subjects in the form of behavior, perception, views, and motivation. Data were collected’ by interview, observation, and study documentation, as the source of information of this study were the stakeholders of Raudlatul Ulum Islamic Boarding School 1 Ganjaran Gondanglegi. Then the data is analyzed by means of a flow model, then the validity of the data is checked by means of the credibility test to test the validity of the data collected.The results of the study are: (1) that studying the yellow book with the sorogan method led directly by the charismatic Kyai Sepuh becomes the santri's expectation in acting and behaving well coupled with the application of the values of the Raudlatul Ulum Ganjaran Islamic boarding school, (2) that the form the implementation of moral values is carried out at the Raudlatul Ulum 1 Islamic boarding school through formal and non-formal education, namely Madrasah Diniyah, Muhadoroh Kubro or Public Speaking activities, recitation of caregivers, Night Consultation, Nadzaman and Tasrifan, Compulsory Education, Bahtsul Masa'il Assembly, Ittihad Musyawarah inter Ma'had, Muhadloroh Kubro, (3) that routine worship activities and students' clothing, religious culture, prayer culture in congregation at all times, and activities of religious value, so that students increasingly motivated to always do things of religious value and train themselves for lunch when students return to their homes. Basedd on the result’s of research and analysis of research data obtained the theory that